Pengaruh Otonomi Daerah Dalam Percepatan Penanganan Covid-19 - Dewi Oktaviyanti; Devi Aprilia; Romadhoni Usflida Sari; Safitri Nur Rohmah; Wahyu Adhi Saputro (Jurnal Manajemen dan Bisnis, 2020)
ABSTRACTIn the current condition, the Covid-19 pandemic has an impact that is enough to make everyone feel distress until the government really carries out regional autonomy appropriately. The Covid-19 pandemic is not over and causes a lot of adversity, especially for the community both in terms of income and social aspects. This study aims to 1) analyze the regional policies that have been applied in dealing with a pandemic 2) Look at the influence of local policies on the socio-economic conditions of the community. The method used in this study is the analytical descriptive method approach. The data used are analytic qualitative data and literature literature study. Based on the results and discussion in this study, regional autonomy policy allows regional governments to freely apply large-scale social restrictions with quarantine or temporary lockdown in order to stop covid-19 transmission. Local government policy has a significant influence on the handling of Covid-19 due to the potential potential of workers who stop working as much as 16% so that the government reopens economic places such as the market as an effort to improve the economy and the welfare of the community who are sinking while continuing to implement health protocols.